A case of a Jordanian male twin with Cohen's syndrome, with genetic analysis and muscle biopsy; case report. (November 2021) - Ghzawi, Ansam; Hirbawi, Hawazen; Negida, Ahmad; Abu-Farsakh, Hussam
Abstract: Introduction and importance: Cohen's syndrome is a rare autosomal recessive developmental disorder. It usually presents with a wide variety of muscular, neurological and ophthalmological clinical features. In this report, we present a rare case of the first Jordanian male identical twin with Cohen syndrome with the first ever muscle biopsy results reported. Case presentation: A 20 months old identical male twins were presented for follow up with history of Salam seaziure, muscle dystocia and signs of development delay since five months old. A muscle biopsy and genetic analysis were done accordingly. Under light microscopy, the H&E and Trichome stains sections showed muscle fibers with minimal variation in muscle fiber size. No muscular degeneration, fat replacement, or fibrosis in the periendomysial area. Increased fibroblasts proliferation was seen in between the muscle fibers. The Dystrophy panel including Dystrophin, Dysferlin, Adhalin (alpha 1 sacroglycan) and Emerin showed a normal staining pattern. The heterozygous mutation pattern seen in the vacuolar protein sorting 13 homolog B (VPS13B) gene is a pathogenic variant of Cohen syndrome. The diagnosis was done accordingly. Conclusion: To the best of our knowledge, this is the first case report of Cohen's syndrome from the Jordanian population, and the first muscle biopsy report in a Cohen's syndrome patient ever. This makes a unique educational report and a good guidance for future research in this concern. Highlights: Cohen's syndrome is a rare autosomal recessive developmental disorder. Cohen's syndrome is a rare genetic disorder that presents with developmental delay, intellectual disability, and eye manifestations. The usual method of testing or screening for Cohen syndrome is VPS13B next-generation sequencing.